RENAL TRANSPLANT IN A PATIENT WITH AUGMENTATION CYSTOPLASTY - Farouk, Khalid; Bano, Uzma; Gondal, Murtaza (Journal of Ayub Medical College Abbottabad, 2007)
A 20 years old girl, had undergone surgery for meningocele six weeks after birth, suffered from neurogenic bladder dysfunction. She underwent an augmentation ileocystoplasty and was trained to perform clean intermittent self catheterization (CISC). After two years she developed renal failure secondary to recurrent urinary tract infections and she was started on chronic hemodialysis. On account of repeated line sepsis, a live related donor renal transplant was performed. About three months after renal transplantation she reported in emergency with an episode of graft rejection secondary to severe infection and later on complicated by leakage of urine from the renal pelvis of the allograft into the peritoneal cavity suggestive of a rent. A percutaneous nephrostomy of the allograft was performed which facilitated healing of the rent in the renal pelvis. The nephrostomy was withdrawn and patient started voiding through urethral catheter and gradually returned to CISC. Keywords: Renal transplant; Augmentation cystoplasty; Renal failure